Między literaturą a polityką ? prywatność w prozie rozrachunków inteligenckich (1946-1948) = Between literature and politics ? privacy in the prose of intelligent settlements (1946-1948) - Kozłowska, Izabela (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The subject of the article is the prose dealing with intelligentsia settlements, published in the years 1946-1948 ("Drewniany koń" ["Wooden horse"] by K. Brandys, "Jezioro Bodeńskie" ["The Constance Lake"] by S. Dygat, "Nagrobek" ["Tombstone"] by S. Otwinowski and P. Hertz's short story collection entitled "Sedan"). Narrative strategy present in the literary works fosters the search for autobiographical elements.
Keywords: proza rozrachunkowa; polityka a literatura; the literature of retribution; politics and literature